A General Survey of Qianjin Weir - Guo, Lingzhi (Journal of Social Science and Humanities, 2026)
Qianjin Weir is located on the outskirts of Fuzhou City, Jiangxi Province. It is an ancient water conservancy project at the diversion junction of the Fu River and Ganggan River. Operating in coordination with the Zhongzhou Embankment Irrigation and Drainage Project, it forms a complete ancient water conservancy irrigation system and is known as “the Dujiangyan of Linchuan”. Having undergone construction and maintenance across the Tang, Song, Yuan, Ming dynasties and the Republic of China period, the existing weir structure remains from the large-scale renovation in the 4th year of the Tianqi reign of the Ming Dynasty (1624). Built with dry-stone masonry techniques, it still plays an important role after hundreds of years of vicissitudes. This paper systematically reviews Qianjin Weir from three perspectives: historical evolution, scientific and technological connotation and cultural inheritance, and explores its historical value, scientific and technological achievements as well as cultural significance as an ancient water conservancy project.